Academic Senate Minutes 2007-12-13 - Academic Senate:::::::::
Chair Report. Associated Student Report. Approval of minutes of 10/11/07. Engineering Science Revision approved. Anthropology and Linguistics revision moved to business and approved. Update on WASC. Discontinuance of TESL program – First Reading. Revision of Grade Appeal Procedures approved. President Report. Provost Report. Vice President of Administration and Finance Report. Focus the Nation Resolution approved. Ad-Hoc Committee: Resolution regarding Independent Audit of Grants and Contracts on Campus and the California Institute on Human Services amended and referred back to Ad-Hoc Committee.